2020
DOI: 10.1186/s12866-019-1672-7
|View full text |Cite
|
Sign up to set email alerts
|

An improved bind-n-seq strategy to determine protein-DNA interactions validated using the bacterial transcriptional regulator YipR

Abstract: BackgroundInteractions between transcription factors and DNA lie at the centre of many biological processes including DNA recombination, replication, repair and transcription. Most bacteria encode diverse proteins that act as transcription factors to regulate various traits. Several technologies for identifying protein–DNA interactions at the genomic level have been developed. Bind-n-seq is a high-throughput in vitro method first deployed to analyse DNA interactions associated with eukaryotic zinc-finger prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
88
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 26 publications
12
88
1
Order By: Relevance
“…While Tan et al [ 15 ] demonstrated a higher Firmicutes/Bacteroidetes ratio in cases with acute ischemic stroke, Haak et al [ 14 ] reported no difference in Firmicutes/Bacteroidetes ratio between cases and controls. In fact, a recent study showed that Firmicutes/Bacteroidetes ratio increased with age in healthy subject [ 44 ]. The study observed Firmicutes was significantly 40% higher in elderly (60–69 years group) as compared to children (0–9 years group), while Bacteroidetes tended to be remarkably 80% lower in the elderly [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Tan et al [ 15 ] demonstrated a higher Firmicutes/Bacteroidetes ratio in cases with acute ischemic stroke, Haak et al [ 14 ] reported no difference in Firmicutes/Bacteroidetes ratio between cases and controls. In fact, a recent study showed that Firmicutes/Bacteroidetes ratio increased with age in healthy subject [ 44 ]. The study observed Firmicutes was significantly 40% higher in elderly (60–69 years group) as compared to children (0–9 years group), while Bacteroidetes tended to be remarkably 80% lower in the elderly [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent study showed that Firmicutes/Bacteroidetes ratio increased with age in healthy subject [ 44 ]. The study observed Firmicutes was significantly 40% higher in elderly (60–69 years group) as compared to children (0–9 years group), while Bacteroidetes tended to be remarkably 80% lower in the elderly [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Izano et al (2008) reported that DNase I prevented biofilm formation of S. aureus and S. epidermidis . DNase I began to dissolve biofilms of Bacillus subtilis after 3 h, whereas the biofilms dissolved at the slight degree at the 24 and 48 h ( Peng et al 2020 ). In addition, Peng et al (2020) reported that young biofilms were easily disturbed by DNase I, whereas the latter was not effective against aged biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…3 and 4 ). Although none of these was ubiquitous in groundwater environments, all have previously been detected in hot springs and in soils ( Alcorta et al, 2018 ; Zhang et al, 2020 ). The phylum Patescibacteria was highly represented in DW1 and DW6.…”
Section: Discussionmentioning
confidence: 96%